Childbirth: the power of human creator - Mohd Arifin, Siti Roshaidai (2017)
Labour is a process by which the products of conception are expelled from the uterus. This talk was delivered to healthcare practitioners at labour room, IIUM Medical Centre. It includes four stages of labour (Stage 1- Stage 4). A simulation of the childbirth process was conducted after the talk.